2009
DOI: 10.1111/j.1365-2311.2009.01102.x
|View full text |Cite
|
Sign up to set email alerts
|

Aggression in imported fire ants: an explanation for shifts in their spatial distributions in Southern United States?

Abstract: 1. The imported fire ants, Solenopsis invicta Buren (red), S. richteri Forel (black), and their hybrids (S. invicta × S. richteri) are sympatric congeners with overlapping but shifting spatial distributions in northern Alabama and Mississippi, United States. 2. The abilities of workers of the three ant forms (or species) to recognise non‐nestmate conspecifics and heterospecifics were compared in separate aggression bioassays using three group sizes of competitor numbers (battles): 1‐1, 5‐1, and 5‐5 resident–in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
17
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 53 publications
(82 reference statements)
4
17
0
Order By: Relevance
“…Our data confirms that whole body soaking with hexane was an effective method for venom alkaloid extraction Ross et al 1987;Fadamiro et al 2009;Eliyahu et al 2011), and fully represents the alkaloids found in the venom sac. It has been proposed that the ratio of cis-C11 to trans-C11 in venom sampled by milking was always higher than that obtained by soaking (Lai et al 2009).…”
Section: Discussionsupporting
confidence: 73%
“…Our data confirms that whole body soaking with hexane was an effective method for venom alkaloid extraction Ross et al 1987;Fadamiro et al 2009;Eliyahu et al 2011), and fully represents the alkaloids found in the venom sac. It has been proposed that the ratio of cis-C11 to trans-C11 in venom sampled by milking was always higher than that obtained by soaking (Lai et al 2009).…”
Section: Discussionsupporting
confidence: 73%
“…Each colony was confirmed to be S. richteri, S. invicta, or hybrid by using both alkaloid and hydrocarbon characters [4] [52]. About 50 randomly selected worker ants from each colony were soaked in 1 ml of hexane for 2 h. One ml of hexane extract was directly injected into a Shimadzu GC17A equipped with an Rtx -1MS column.…”
Section: 'mentioning
confidence: 99%
“…, 2009). Colony mates are usually ignored, whereas other hetero‐ and conspecifics typically elicit an aggressive response (Stuart, 1993; Fadamiro et al. , 2009; Menzel et al.…”
Section: Introductionmentioning
confidence: 99%
“…Workers inspect the hydrocarbon profiles of other workers with their antennae and are thought to discriminate according to the degree to which it overlaps their own template (Suarez et al, 2002;van Zweden et al, 2009). Colony mates are usually ignored, whereas other hetero-and conspecifics typically elicit an aggressive response (Stuart, 1993;Fadamiro et al, 2009;Menzel et al, 2009).…”
Section: Introductionmentioning
confidence: 99%